Life Strategy of Female Farm Workers at PT. Toba Pulp Lestari After Divorce - Sitorus, Ida Kristina; Achmad, Nurman; Daulay, Harmona (East Asian Journal of Multidisciplinary Research, 2025)
This study examines the survival strategies of female daily laborers at PT. Toba Pulp Lestari following divorce. The main focus is to understand the social and economic dynamics experienced by these women as they face life challenges post-divorce. The research employs a qualitative approach with a case study method, utilizing in-depth interviews and participatory observations as data collection techniques. The findings reveal that female daily laborers adopt various strategies to survive, including leveraging social networks, and managing finances strictly. Support from family, local communities, and social organizations plays a crucial role in helping them cope with economic pressures and the social stigma often associated with divorce. However, the study also highlights that limited access to education and skill training poses significant barriers to improving their quality of life.